Physical Activity in Individuals with Down Syndrome: Measurement with Pedometer Use - Μantsos Ευάγγελος; Katsarou Δήμητρα; Κourtessis Θωμάς; Vernadakis Νικόλαος; Μichalopoulou Μαρία; Zisi Βασιλική (Inquiries in Physical Education and Sport, 2019)
The purpose of this study was the measurement of physical activity of two groups of people with Down Syndrome (group with high physical activity and group with low physical activity) with pedometers during a week and during a week-end. Participants were tested both in steps and in aerobic steps. Participants in the current study were 27 people with Down Syndrome, aged 16 to 44 yrs. The pedometer OMRON Walking Style Pro was used for the steps and aerobic steps and the questionnaire PDPAR for additional information regarding time, space and people present at the activity. A 2-way ANOVA yielded a main effect of the Day (p<.01,) και the Group (p<.001) in general physical activity, whereas in aerobic steps a 2-way ANOVA yielded a main effect only of the Group (p<.05). In conclusion, it is necessary to identify all the factors that contribute to the physical activity of people with Down Syndrome in order to organize programs within or out of school curriculum, which will help them to improve physical activity and, therefore, their quality of life.